Assessment of equine piroplasmids in the Nhecolândia sub-region of Brazilian Pantanal wetland using serological, parasitological, molecular, and hematological approaches - Campos, João B.V.; André, Marcos R. [UNESP]; Gonçalves, Luiz R. [UNESP]; Freschi, Carla R. [UNESP]; Santos, Filipe M.; de Oliveira, Carina E.; Piranda, Eliane M.; de Andrade, Gisele B.; Macedo, Gabriel C.; Machado, Rosangela Z. [UNESP]; Herrera, Heitor M. (Elsevier, 2019)
Brazilian Pantanal is the world´s largest wetland ecosystem, where cattle's ranching is the most important economic activity. The objective of this study was to compile some epidemiological features on equine piroplasmids from the Nhecolândia sub-region of Pantanal wetland through the evaluation of the patterns of T. equi and B. caballi infections in different groups of horses; identification of the tick species that infest horses; and to study phylogenetic relationships among Theileria equi 18S rRNA gene sequences. During October 2015, blood and serum samples were collected from 170 horses in four different categories. Ticks, after identification, had their hemolymph and eggs examined for the presence of piroplasmid sporokinets. Also we searched parasites in the peripheral blood smears of the investigated horses. The number of red blood cells (RBCs) and the packed cell volume (PCV) ​​were determined to test for anemia in the infected animals, and exposure to B. caballi and T. equi was evaluated by enzyme-linked immunosorbent assay. “Catch all primers” based on 18S rRNA gene were used in polymerase chain reactions (PCR) to detect equine piroplasmids, followed by three nested PCRs for the phylogenetic analysis. The serological results showed that 61.8% and 52.9% of the horses sampled were exposed to T. equi and B. caballi, respectively. Piroplasmid DNA was detected in 43.5% of the horses analyzed. Our sequencing revealed 98–100% identity with some sequences previously published in GenBank for T. equi, and microheterogeneity among others. We found that 51.2% of the animals sampled were infested with Dermacentor nitens, Amblyomma sculptum, and Rhipicephalus (Boophilus) microplus, singly or co-infested. Since positive and negative animals presented similar RBC and PCV values, and no sporokinets were found on blood smears, hemolymph and eggs of the ticks collected, we suggest that infected equines can act as asymptomatic carriers for piroplasmosis in the studied region. Our results together showed the enzootic characteristic of equine piroplasmids in Pantanal region highlighting the importance of using different methods for detection these parasites. Moreover, breeding mares and foals should be monitored since they displayed the greatest occurrences for molecular test (59.0% and 86.1% respectively) and tick infestations (87.2% and 63.9% respectively).
Keywords: Babesia caballi; ELISA; Pantanal; PCR; Theileria equi; Ticks